DEVELOPMENT OF CELL CULTURE FROM CAUDAL FIN AND HEART OF TOR TOR (HAMILTON-BUCHANAN) - Kamalendra, Kamalendra; Lakra, W. S.; Sharma, J.; Goswami, M.; Sharma, B. S. (Journal of Indian Fisheries Association, 2010)
Tor mahseer (Tor tor), possess high commercial and recreational value as they are potential game as well as food fish of India. Tow cell culture systems were developed from fin and heart of T. tor (Hamilton-Buchanan). The explants excised aseptically from fingerling of T. tor were cultured in Leibovitz-15 (L-15) medium with 20% fetal bovine serum (FBS). Radiation of cell started after 72 hours and 48 hours of explant attachment from caudal fin and heart respectively. Confluent monolayer of cell with heterogeneous morphology around fin explants was observed after 7-10 days, where as a homogenous confluent layer of fibroblastic cell from heart explants was observed after 12-13 days. The establishment of cell culture systems from different organs and tissues of commercial important species would facilitates in vitro research. Â Key words: Cell culture, Caudal fin, Heart, Tor tor.